Characterization comparison of bottom ash and fly ash during gasification of agricultural residues at an industrial-scale gasification plant – Experiments and analysis. (1st February 2021) - Yao, Xiwen; Mao, Jianyu; Li, Li; Sun, Lu; Xu, Keqiang; Ma, Xingzong; Hu, Yonglu; Zhao, Zhicheng; Chen, Shoukun; Xu, Kaili
Highlights: Rounded forms of fly particles could be regarded as the indicative of ash melting. Co-existence of slvite and potassium silicates served as adhesive for ash deposition. Fouling index ( F u ) value of cyclone ash ( F u = 41.2) was the highest in studied ashes. Comparison of thermograms indicated the high content of organics in the bottom ash. Abstract: In this study, the characterization of the fly and bottom ashes from an industrial gasification plant for biomass syngas production were investigated and compared in terms of particle size distribution, chemical composition, fusibility, mineralogy and morphology. The experimental results indicated that the characteristic particle sizes of the bottom ashes from gasifier were larger than those of the fly ashes from cyclone or sprayer. By contrast, the fly ashes contained higher contents of potassium, sulphur and chlorine. The base-to-acid ratio ( R b/a ) values for those fine fractions in the bottom residues and the fly particles from cyclone were in high deposition range ( R b/a > 1.0) while that for the slags in the bottom ash or the fly particles from sprayer was in medium deposition range (0.5–1.0). As regards the fouling index ( F u ), the value of cyclone ash ( F u = 41.2) was higher than those of the other ashes, reflecting its relatively higher deposition tendency on heat transfer surfaces. Besides, the fusion temperatures of the fly ashes were lower than those of bottom ashes. The rounded forms of fly particles could be regarded as the indicative of ash melting. Comparison of thermograms indicated that the bottom ash contained more organics than fly ash, thus explaining its relatively higher weight loss during ash fusion. In practice, more attention should be paid on the rational control of operating temperature, which could relieve the occurrence of ash deposition/agglomeration to some extent.